Increase in cases of malaria in Mozambique, 2014: epidemic or new endemic pattern? - Jorge Alexandre Harrison Arroz (Universidade de São Paulo, 2016)
ABSTRACT OBJECTIVE To describe the increase in cases of malaria in Mozambique. METHODS Cross-sectional study conducted in 2014, in Mozambique with national weekly epidemiological bulletin data. I analyzed the number of recorded cases in the 2009-2013 period, which led to the creation of an endemic channel using the quartile and C-Sum methods. Monthly incidence rates were calculated for the first half of 2014, making it possible to determine the pattern of endemicity. Months in which the incidence rates exceeded the third quartile or line C-sum were declared as epidemic months. RESULTS The provinces of Nampula, Zambezia, Sofala, and Inhambane accounted for 52.7% of all cases in the first half of 2014. Also during this period, the provinces of Nampula, Sofala and Tete were responsible for 54.9% of the deaths from malaria. The incidence rates of malaria in children, and in all ages, have showed patterns in the epidemic zone. For all ages, the incidence rate has peaked in April (2,573 cases/100,000 inhabitants). CONCLUSIONS The results suggest the occurrence of an epidemic pattern of malaria in the first half of 2014 in Mozambique. It is strategic to have a more accurate surveillance at all levels (central, provincial and district) to target prevention and control interventions in a timely manner.